Reconstruint la biografia del mudèjar valencià ʿAbd Allāh b. Al-Ṣabbāḥ: dades sobre València (segles XIV-XV). - CONSTÁN-NAVA, ANTONIO (Scripta)
The origin of the Mudéjar ʿAbd Allāh b. al-Ṣabbāḥ (AH 14th-15th c.) remains a mystery. The data that exist in his only known work do not say anything about him; nor is he mentioned in any medieval work. The study brings together all that is known about his origin and focuses on certain passages in his work that seem to refer his origin to Valencian lands, specifically, between the cities of València and Xàtiva. On the one hand, the study focuses on these parts of the narrative, from which specific information is extracted that may shed light on the biography of Ibn al-Ṣabbāḥ; and, on the other hand, all the mentions that the Mudejar made about the Valencian territory will be extracted in order to support the hypothesis of his Valencian origin. It also focuses on the nasab «al-Ṣabbāḥ» that appeared throughout the Valencian territory between the 13th and 17th centuries. The texts that are examined and quoted are presented translated into Valencian, in what is intended to be a partial advance of the translation into Valencian of the work of this Mudejar traveller, most probably from the Crown of Aragon.